(untitled) - Malcolm, J. S.

Chemical etching investigation on surface finish and fatigue behaviour of laser powder bed fusion produced Ti-6Al- 4V. (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.